Mapping Global Research Trends on Job Insecurity: A Bibliometric Analysis of Labor Force Transformation - Rahmat Hidayat; Syamsul Bahri (ARBITRASE: Journal of Economics and Accounting, 2026)
The available literature on job insecurity exists in various disciplines, using a variety of theoretical frameworks and indicators, thus giving rise to the need to systematically map the structure of knowledge and the direction of findings. This study aims to map the global development of research on job insecurity in the context of workforce transformation, especially due to digitalization, automation, organizational change, and psychological dynamics of workers. In addition, this study also identifies publication trends, key scientific actors, dominant countries, keyword relationships, as well as thematic clusters that make up the knowledge structure of this field. The method used is a bibliometric analysis based on Scopus data with the search keyword "job insecurity". Document selection was carried out using the PRISMA approach, for publication in 2016-2025, in the fields of business, management and accounting and psychology, types of article documents, and English-language journal sources. The data is analyzed using VOSviewer through network mapping and visualization. The results of the study show a significant increase in publications on job insecurity, with a peak in 2025 of 219 documents. This study is dominated by the fields of social sciences, management, and psychology. The United States, China, and the United Kingdom are the most prolific countries, while Jiang, De Witte, and Probst are among the lead authors. This study recommends that future researchers combine various methods for bibliometric research, such as using the B-SLR method, which is a bibliometric method combined with a systematic literature review.